2015
DOI: 10.3382/ps/pev252
|View full text |Cite
|
Sign up to set email alerts
|

In ovo feeding with minerals and vitamin D3 improves bone properties in hatchlings and mature broilers

Abstract: The objective of this study was to examine the effect of in ovo feeding (IOF) with inorganic minerals or organic minerals and vitamin D3 on bone properties and mineral consumption. Eggs were incubated and divided into 4 groups: IOF with organic minerals, phosphate, and vitamin D3 (IOF-OMD); IOF with inorganic minerals and phosphate (IOF-IM); sham; and non-treated controls (NTC). IOF was performed on embryonic day (E) 17; tibiae and yolk samples were taken on E19 and E21. Post-hatch, only chicks from the IOF-OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 53 publications
1
31
1
1
Order By: Relevance
“…Similar growth patterns of the trabecular bone have been reported recently in chickens [28], geese [41] and in humans [42]. The tibiotarsal mechanical properties such as rigidity, maximal strength, and fracture strength are indicators of skeletal integrity and associated with differing bone characteristics including both densitometric (cortical and trabecular BMDv) and geometric parameters (bone weight, bone weight per unit of length, bone width, total and cortical bone area) [23,32,43]. Our results show that the bone volume fraction decreases with age in both chicken lines, resulted from the reduction in trabecular numbers over time with unchanged trabecular thickness, which could diminish the bone fracture strength.…”
Section: Plos Onesupporting
confidence: 65%
“…Similar growth patterns of the trabecular bone have been reported recently in chickens [28], geese [41] and in humans [42]. The tibiotarsal mechanical properties such as rigidity, maximal strength, and fracture strength are indicators of skeletal integrity and associated with differing bone characteristics including both densitometric (cortical and trabecular BMDv) and geometric parameters (bone weight, bone weight per unit of length, bone width, total and cortical bone area) [23,32,43]. Our results show that the bone volume fraction decreases with age in both chicken lines, resulted from the reduction in trabecular numbers over time with unchanged trabecular thickness, which could diminish the bone fracture strength.…”
Section: Plos Onesupporting
confidence: 65%
“…There were no significant differences among treatments for chick weight, yolk sac weight, liver weight, and heart weight. Similarly, Oliveira et al (2015) and Yair et al (2015) reported that injection of mineral mixtures with different Mn (from 0.013 to 0.039 mg per egg) content into the egg did not affect hatching weight in broilers.…”
Section: Resultsmentioning
confidence: 91%
“…In previous studies, no studies have been conducted to report the effects of treatments on chick length. However, Oliveira et al (2015) and Yair et al (2015) showed that injection of mineral mixtures with different Mn (from 0.013 to 0.039 mg per egg) content into the egg did not affect tibia length in broilers. Contrary to the present study, early studies have reported that Mn deficiency in the diet causes shortness of legs and beaks in chicks (Caskey andNorris 1939).…”
Section: Resultsmentioning
confidence: 94%
“…One way to stimulate early development of the gastrointestinal tract is to ensure the presence of highly digestible nutrients before and immediately after hatching (Noy and Uni, ). This has been achieved with the use of pre‐housing nutrition (Careghi et al., ) or in ovo feeding (Tako et al., ; Grodzik et al., ; Yair et al., ).…”
Section: Introductionmentioning
confidence: 99%